DEVELOPMENT OF ALT.MINE.ID STARTUP FOR CRYPTOCURRENCY MINING FOR INVESTORS IN INDONESIA - Al Arif Rahmadika Putra Wicaksono; Sri Hariyani Eko Wulandari; Julianto Lemantara (Jurnal Sistem Informasi Universitas Dinamika, 2019)
ALT.Mine.ID is a startup engaged in the field of cryptocurrency, especially in the mining sector. Currency conversion fees that are too large and mining contracts that can be decided at any time by the company when purchasing hashrates using cloud mining abroad are one of the obstacles faced by local miners. In addition, independent miners also complain about the amount of capital that must be spent to start their business. Coupled with maintenance errors and overclocking of hardware that can occur causing damage to mining hardware.The solution based on the above problems is to create a website-based startup application that will be named ALT.Mine.ID to manage the cryptocurrency mining process. Through the ALT.Mine.ID startup application investors and miners can monitor hardware and balance income from mining anytime and anywhere.The results show that this application can cut the conversion costs that must be paid because the payment system uses local bank transfers. Besides that the mining contract will not stop in the middle of the road because maintenance costs are charged at the beginning of the hashrate purchase. Overclocking errors and hadware maintenance will fully be the responsibility of the startup provider so that miners don't need to think about how to do hardware maintenance.